Carbon Footprint of Electricity Produced in the Russian Federation - Ekaterina Shirinkina; Yuliya Mozzhegorova; Galina Ilinykh; Vladimir Korotaev (Energies)
Energy generation makes a significant contribution to greenhouse gas emission. The carbon footprint of electricity significantly affects the total carbon footprint of a wide variety of products, which is especially relevant for energy-intensive industries (aluminum, platinum, carbon fiber-reinforced plastics, etc.) and hydrogen energy. The carbon footprint of aluminum, produced in Russia is 8.0–15.0 kg CO2-eq./kg. It is lower than the actual carbon footprint of aluminum produced in other countries due to the lower carbon intensity of Russian grid electricity in comparison with the world average. The carbon footprint of hydrogen, produced by photovoltaic modules with electricity consumption from the Russian national electricity grid is 16.6 kg CO2-eq./kg, while the world average carbon footprint of photovoltaic hydrogen is 18.1 kg CO2-eq./kg. The average carbon footprint of electricity generated and consumed in Russia ranges from 310 to 634 g CO2-eq./kWh. This paper analyzes methodological approaches to determining grid emission factors for Russian electricity. It has been established that different principles of spatial division of the Russian energy system can be used to determine grid emission factors (national average grid emission factor, grid emission factors for the integrated energy system, grid emission factors for price and non-price zones of the wholesale electricity market).